2019
DOI: 10.3389/fpsyg.2019.01525
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spirituality and Religiosity in Subjective Well-Being of Individuals With Different Religious Status

Abstract: Spirituality and religiosity have been found to be positive predictors of subjective well-being, even if results are not altogether consistent across studies. This mixed evidence is probably due to the inadequate operationalization of the constructs as well as the neglect of the moderation effect that the individuals’ religious status can have on the relation between spirituality/religiosity and subjective well-being. The current study aimed to investigate the relationship of spirituality and religiosity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
149
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(170 citation statements)
references
References 85 publications
16
149
0
5
Order By: Relevance
“…church attendance) and subjective wellbeing Gartner, Larson, & Allen, 1991;Krause, 2011), particularly in old age (Krause & Hayward, 2016;Boey, 2003). Consistent with previous studies, religious engagement was found to have a positive impact both on the induction of positive emotions and on satisfaction with life, both among churchgoers per se and in terms of the spirituality domain of wellbeing, which fosters a greater sense of coherence and meaning in life (Villani, Sorgente, Iannello, & Antonietti, 2019;Von Humboldt et al, 2015). A study by Ellison (1991) has found that religious individuals with strong faith have higher levels of wellbeing, greater subjective happiness, and better psychosocial adjustment after stressful life events.…”
Section: Discussionsupporting
confidence: 83%
“…church attendance) and subjective wellbeing Gartner, Larson, & Allen, 1991;Krause, 2011), particularly in old age (Krause & Hayward, 2016;Boey, 2003). Consistent with previous studies, religious engagement was found to have a positive impact both on the induction of positive emotions and on satisfaction with life, both among churchgoers per se and in terms of the spirituality domain of wellbeing, which fosters a greater sense of coherence and meaning in life (Villani, Sorgente, Iannello, & Antonietti, 2019;Von Humboldt et al, 2015). A study by Ellison (1991) has found that religious individuals with strong faith have higher levels of wellbeing, greater subjective happiness, and better psychosocial adjustment after stressful life events.…”
Section: Discussionsupporting
confidence: 83%
“…Religion can be conceptualized as a complex and multifaceted phenomenon involving elements of belief, behavior, community involvement, and social identity [30]. On the other hand, spirituality can be viewed as the search for interconnectedness with humanity and a personal need for connection with a higher power that can occur in and/or outside of a formal religious context [10]. A very large number of studies have found a relationship of religious and spiritual involvement with better psychological and health outcomes [31], with these effects often appearing more pronounced in later life [32].…”
Section: Theme Ii: the Role Of Religion And Spiritualitymentioning
confidence: 99%
“…Contrary to the negative myths that relate aging with declines in well-being, Carstensen and colleagues [9] suggest that older adulthood is a period of development where the well-being outcomes and emotional regulation of the elderly are improving compared to the middle-life because older adults tend to focus particularly on emotionally positive situations. Furthermore, a growing body of research reveals that involvement in religious activities affects spiritual well-being and may improve the elderly's overall psychological well-being and the way that they judge their life satisfaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades studies have highlighted the ways that religious involvement conceptualized as "observable feelings, beliefs, activities, and experiences in relation to the spiritual, divine, or supernatural" (p. 239, [12]) contributes to better health outcomes such a lowered risk of mortality [12,13]. Often, the terms, religion, spirituality, and faith are used interchangeably within health literature [30]. Within the context of this paper, I will rely on the term "faith" to discuss spiritual-religiosity as "seeking guidance about one's behavior from God, a higher power, spirit, religious texts, or leaders; having belief in, relationship with or connection with any of the entities referenced above" [7].…”
Section: Faith and Healthmentioning
confidence: 99%